OPTIMASI PENEMPATAN DAN KAPASITAS DISTRIBUTED GENERATION (DG) UNTUK MEMINIMALKAN RUGI-RUGI DAYA PADA PENYULANG ABANG MENGGUNAKAN METODE QUANTUM GENETIC ALGORITHM (QGA) - I Gusti Agung Adhi Waskita; Antonius Ibi Weking; Widyadi Setiawan (Jurnal SPEKTRUM, 2019)
This research was conducted to obtain the optimal DG location with the aim of minimizing power losses in feeders. Penyulang Abang has a length of 207,946 kms with power losses of 1,105 MW. One way to reduce power losses is to install distributed generation. Distributed generation is installed in four Abang feeder locations. Optimization is done by using the Quantum Genetic Algorithm (QGA) method. Quantum Genetic Algorithm is an evolutionary algorithm. Genetic Quantum Method Algorithms are based on the concept of quantum bits (qubit) and the superposition of quantum mechanical forms. The purpose of this method is to select the best results from the results obtained. The final result of the QGA method is the most efficient distributed generation and capacity placed in several Abang feeder locations, namely buses 1, 5, 7 and 302 with capacities of 0.374 MW, 1,894 MW, 1,988 MW and 0.500 MW, respectively. So that the power losses are reduced to 0.234 MW.